Students exposure to radio frequency electromagnetic fields in Marmara University - ÇALLIALP KUNTER, Fulya (My University, 2015)
In recent years, there has been increasing public concern about the health implication of electromagnetic (EM) wave exposures due to the electronic sources. For this reason, various public organizations in the world have been established safety guidelines. In this study, electric field strength values are measured at 44 different location points of Marmara University in Göztepe Campus. In addition to the spot measurements, 24 hours measurement is also done to analyze the variation of electric field strength values. The results show that the measured electric field strength values are below the recommended international standard limits.
Keywords: Electromagnetic Pollution, Measurements, Radio Frequency Radiation.